2021
DOI: 10.3390/antiox10030405
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Mitochondrial Dysfunction in Pregnancy Complications

Abstract: Hypoxia is a common and severe stress to an organism’s homeostatic mechanisms, and hypoxia during gestation is associated with significantly increased incidence of maternal complications of preeclampsia, adversely impacting on the fetal development and subsequent risk for cardiovascular and metabolic disease. Human and animal studies have revealed a causative role of increased uterine vascular resistance and placental hypoxia in preeclampsia and fetal/intrauterine growth restriction (FGR/IUGR) associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 331 publications
(209 reference statements)
1
39
0
Order By: Relevance
“…The suppression of NFκB activation and its translocation into nucleus of cells in mice uterus was found to delay the process of implantation confirmed in animal models whereas the complete loss of NFκB activity in knockout mice results in death [ 31 , 32 ]. As implantation proceeds, the oxygen level in the environment increases; this steers trophoblast differentiation toward remodeling of the maternal spiral artery and allows the placenta to mature into an exchange organ [ 33 , 34 ]. The inflammatory reaction is gradually slowed, thus allowing the development of an immunosuppression stage needed to maintain pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppression of NFκB activation and its translocation into nucleus of cells in mice uterus was found to delay the process of implantation confirmed in animal models whereas the complete loss of NFκB activity in knockout mice results in death [ 31 , 32 ]. As implantation proceeds, the oxygen level in the environment increases; this steers trophoblast differentiation toward remodeling of the maternal spiral artery and allows the placenta to mature into an exchange organ [ 33 , 34 ]. The inflammatory reaction is gradually slowed, thus allowing the development of an immunosuppression stage needed to maintain pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, the p53/RSK1 complex plays a dominant role, being responsible for the phosphorylation of NFκB at Serine536 [ 19 , 49 ]. It is known that preeclampsia is related to the accumulation of ROS and inflammatory factors in maternal blood, and that the HTR8/SVneo cell line generates mitochondrial ROS in hypoxic condition [ 34 , 50 , 51 , 52 ]. Therefore, in the present study, the combination of maternal serum and hypoxic conditions certainly influenced the generation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overproduced ROS would overwhelm the endogenous defense mechanisms (SOD, etc. ), further leading to the accumulation of ROS [ 14 , 15 ]. ROS is considered to play a critical role in disease progression after MI [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we showed that padlock assay is a robust method to map the distribution of the SARS-CoV-2 genome in infected tissues, and, most importantly, for the first time we provided images visualizing the in situ co-localization of SARS-CoV-2 RNA and mitochondria in host cells. Furthermore, in the context of pregnancy complications, mitochondrial dysfunction appears a critical feature in the pathogenesis of preeclampsia [10]. To note, pregnant women with COVID-19 are more likely to develop preeclampsia [11].…”
Section: Introductionmentioning
confidence: 99%